(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Prediabetes, an intermediate state of hyperglycemia is the precursor stage of type 2 diabetes mellitus. Prediabetes and diabetes has been emerged as a major challenging health problem worldwide due to their high mortality and morbidity rates. Sedentary lifestyle, unhealthy diet, physical inactivity, mental stress associated with urbanisation contributes the increasing prevalence of Prediabetes and diabetes. Since type 2 diabetes and their complications results in poor quality of life and significant economic burden to family and society due to the increased medical expenditure and loss of productivity, an effective intervention is required. Life style interventions comprising a healthy diet, and physical activity in the prediabetic stage will be a best measure to halt the further progression in to type 2 diabetes. In this study an Ayurvedic diet, Mudgadi Kashaya peya and selected yoga techniques were given for a period of 90 days to evaluate their effect in Prediabetes. Statistical analysis of the data obtained revealed that Mudgadi Kashaya peya and selected yoga techniques has significant effect in reduction of FBS, PPBS, HbA1c and Total Cholesterol values.